Applicability of Law Number 11 of 2020 Concerning Job Creation After The Constitutional Court Decision Number 91/PUU-XVIII/2020 (Pandecta Research Law Journal, 2022)
With the issuance of the decision of Constitutional Court Number 91/PUU-XVIII/2020, the DPR and the government, as lawmakers, are obliged to comply with it. Because the decision of the Constitutional Court is a legal decision that all parties must obey without exception, it is necessary to obtain an assessment, first, of how the law applies. No. 11 of 2020 after the decision of Constitutional Court Number 91/PUU-XVIII/2020. Second, how are the DPR and the government’s efforts to respond to changes in Law no. 11 of 2020 after Constitutional Court Decision Number 91/PUU-XVIII/2020? The research method used is normative legal research, namely library research, whose sources use secondary data in the form of primary, secondary, and tertiary legal materials. The results of the study on the Constitutional Court Decision Number 91/PUU-XVII/2020, that Law No. 11 of 2020 is still valid. However, the House of Representative/DPR and the Government are given time to fix it within a period of two years. If corrections are not made within this time period, the law will become permanently invalid. In fulfilling this, first amendments were made to Law Number 12 of 2011, so that it became Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 concerning Formation of Legislation. The amendment has included the omnibus method as the basis for forming laws and regulations. Based on Law Number 13 of 2022, the DPR and the Government made improvements to Law Number 11 of 2020. The results of the study show that by the decision of the Constitutional Court Number 91/PUU-XVIII/2020, which grants the applicant’s request conditionally, the DPR and the government are obliged to amend Law no. 11 of 2020 concerning Job Creation since the decision of the Constitutional Court aquo was read. If, within 2 (two) years, the DPR and the government cannot make improvements to Law No. 11 of 2020, the law becomes permanently unconstitutional. On that basis, law. No. 11 of 2020 after the decision of the Constitutional Court Number 91/PUU-XVIII/2020 is still valid unless the DPR and the government do not make improvements to Law No. 11 of 2020 within 2 (two) years, then the law becomes permanently invalid. Therefore, in response to the Constitutional Court’s decision, the DPR and the government are currently trying to amend Law no. 12 of 2011 concerning the Establishment of Legislation. In this change, the omnibus law method is explicitly mentioned as one of the methods for forming laws.